THE IMPACT OF 2-AMINOETHANESULFONIC ACID, GUARANINE METHYL THEOBROMINE 1, 3, 7-TRIMETHYLXANTHINE THEINE AND/OR ISOBUTYLPHENYL PROPIONIC ACID ON MASCULINE FECUNDITY, AND MORPHOPATHOLOGICAL DISORDERS IN RATS: Teratogenic effect of Ibuprofen, Taurine and Caffiene on Masculine Fecundity - WAEL ABU DAYYIH; YAZAN S BATARSEH; ZAINAB ZAKAREIA; MOHAMED HAMMAD; KAMAL MANSI; WALID ABU RAYYAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: This study aims to evaluate the impact of caffeine (CAF), taurine (TUR), and ibuprofen (IBF) consumption on the masculine fecundity in rats and fetuses development. Methods: The 1st group was kept as a normal control received distilled water. The 2nd, 3rd, and 4th groups received orally 250 mg/kg, 40 mg/kg, and 270 mg/kg of TUR, CAF, and IBF, respectively. In addition, the 5th, 6th, 7th, and 8th groups received TUR with CAF, TUR with IBF, CAF with IBF, and TUR, CAF, IBF combination, for 45 days. Blood samples were taken to determine testosterone and follicle-stimulating hormone levels and oxidation levels. Moreover, in testes, malondialdehyde and nitrite/nitrate were estimated. Besides, the abnormality of sperms, sperm counts, and percentage of sperm motilities was characterized. These masculines were allowed to mate with untreated masculine rats to determine the rate of pregnancy and study any malformation in their fetuses. Results: The study revealed that each of CAF and/or IBF decreased the weights of fetuses, as well as sperm counts and motilities significantly. Besides, percentages of head and tail abnormalities were increased in CAF and/or IBF. The histopathological examination revealed the presence of marked degenerative changes in testes in CAF and/or IBF-treated groups. Conclusion: CAF and IBF have a teratogenic effect on spermatozoa and masculine fecundity, whereas TUR almost improved undesirable impacts induced by IBF or/and CAF.